2001
DOI: 10.1897/1551-5028(2001)020<1927:aocasf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 137cesium and 90strontium From Abiotic and Biotic Sources in Rodents at Chornobyl, Ukraine

Abstract: Bank voles (Clethrionomys glareolus) and laboratory strains of house mice (Mus musculus BALB and C57BL) were relocated into enclosures in a highly contaminated area of the Red Forest near the Chornobyl (Ukraine) Reactor 4 to evaluate the uptake rates of 137Cs and 90Sr from abiotic sources. Mice were provided with uncontaminated food supplies, ensuring that uptake of radionuclides was through soil ingestion, inhalation, or water. Mice were sampled before introduction and were reanalyzed every 10 d for 137Cs upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 18 publications
1
44
1
Order By: Relevance
“…Detailed studies on accumulation, distribution and excretion of radionuclides have been conducted for a long time, but primarily regarding agricultural and laboratory animals (Buldakov and Moskalev 1968; Aleksakhin 1982;Korneev and Sirotkin 1987;Moskalev 1989; Vandecasteele et al 1989), and, therefore, they are not fully applicable for extrapolation to wild species. There has been very little applicable information available on wild animals inhabiting the ChEZ (Kozlo et al 1998;Chesser et al 2000Chesser et al , 2001Gaychenko et al 2001;Oleksyk et al 2002; Ryabokon et al 2005; Taskaev et al 1990). In view of this, in 1998 -2010, the International Radioecology Laboratory (IRL) performed a wide range of studies on accumulation and metabolism of radionuclides, as well as on dose rates, in wild murine rodents and shrews under the actual conditions of the ChEZ.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies on accumulation, distribution and excretion of radionuclides have been conducted for a long time, but primarily regarding agricultural and laboratory animals (Buldakov and Moskalev 1968; Aleksakhin 1982;Korneev and Sirotkin 1987;Moskalev 1989; Vandecasteele et al 1989), and, therefore, they are not fully applicable for extrapolation to wild species. There has been very little applicable information available on wild animals inhabiting the ChEZ (Kozlo et al 1998;Chesser et al 2000Chesser et al , 2001Gaychenko et al 2001;Oleksyk et al 2002; Ryabokon et al 2005; Taskaev et al 1990). In view of this, in 1998 -2010, the International Radioecology Laboratory (IRL) performed a wide range of studies on accumulation and metabolism of radionuclides, as well as on dose rates, in wild murine rodents and shrews under the actual conditions of the ChEZ.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that wildlife within the zone continue to accumulate substantial amounts of radionuclides (Chesser et al . ; Geras'kin et al . ); other research has uncovered a range of negative health impacts on wildlife, including sperm deformities and increases in mutation rates, morbidity, and mortality (Møller et al .…”
mentioning
confidence: 99%
“…The number of unstable atoms of 137 Cs is expected to approach a constant (i.e., asymptotic) value with time. Therefore, the asymptotic value for the number of unstable atoms of 137 Cs per gram of tissue was calculated according to the method described by Chesser et al [16]. The uptake rate, representing the daily loss rate by physical decay and biological processes, was also calculated for each strain.…”
Section: Resultsmentioning
confidence: 99%
“…Specific activities and concentrations in soil samples from the enclosures were 1,296 Bq g −1 (1.71 × 10 12 unstable atoms/g) for 90 Sr and 3,317 Bq g −1 (4.54 × 10 12 unstable atoms/g) for 137 Cs. Procedures necessary to determine uptake and accumulated dose rates in the enclosures are described in detail by Chesser et al [16] and include animals from this study. The primary interest for the present study was to calculate the dose caused by the uptake of radionuclides for the period after the mice were introduced into the enclosures and to relate that dose to MN induction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation